1997
DOI: 10.1111/1468-5884.00058
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Transmission of Tool Making and Use for Drinking Juice in a Group of Captive Chimpanzees (Pan troglodytes)

Abstract: so on. Recent studies have revealed that each community has its own traditional way of making and using tools (McGrew, 1992(McGrew, , 1994. Although there are still controversies (e.g., Heyes & Galef, 1996;Tomasello, 1996;Visalberghi & Fragaszy, 1990), these skills are considered to be transmitted culturally between communities and across generations (Matsuzawa, 1994;Matsuzawa & Yamakoshi, 1996;Yamakoshi & Matsuzawa, 1993).Wild chimpanzees drink rain water from the hollow of trees using leaves. This tool-use b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
3
19
1
Order By: Relevance
“…The drinking tool-use was also sporadically observed in the previous years at Mahale, suggesting that individual invention occasionally occurred. Perhaps because of the relative ease of inventing a drinking tool, this kind of tool-use for drinking water (or juice) is observed almost universally among wild chimpanzees (Whiten et al 1999) and captive chimpanzees (Kitahara-Frisch and Norikoshi 1982;Takeshita and van Hooff 1996;Tonooka et al 1997;Morimura 2003). Hayashi and Matsuzawa (2003) suggested that the chimpanzee has a strong behavioral tendency to ''insert sticks into holes.''…”
Section: And the Development Of Culturalmentioning
confidence: 99%
“…The drinking tool-use was also sporadically observed in the previous years at Mahale, suggesting that individual invention occasionally occurred. Perhaps because of the relative ease of inventing a drinking tool, this kind of tool-use for drinking water (or juice) is observed almost universally among wild chimpanzees (Whiten et al 1999) and captive chimpanzees (Kitahara-Frisch and Norikoshi 1982;Takeshita and van Hooff 1996;Tonooka et al 1997;Morimura 2003). Hayashi and Matsuzawa (2003) suggested that the chimpanzee has a strong behavioral tendency to ''insert sticks into holes.''…”
Section: And the Development Of Culturalmentioning
confidence: 99%
“…The implications of the failures reported for Povinelli's chimpanzees (2000) are problematic, relative to findings with other captive nonhuman primates (e.g., Deblauwe et al, 2006;Fragaszy et al, 2004;Sakura and Matsuzawa, 1991;Tonooka et al, 1997;Westergaard et al, 1995;Yocom and Boysen, 2010), but especially given the demonstrated prowess of wild chimpanzees in extensive and creative use of objects as tools in their environment. Why would captive chimpanzees not exhibit knowledge of physical support when such capabilities are both advantageous and necessary for their survival in the wild?…”
mentioning
confidence: 96%
“…Since the initial discoveries by Goodall (1964), each year, particularly over the past two decades, research groups from Germany, Japan, Switzerland, the U.S., and other teams continue to report new tool types and functions by wild chimpanzees (e.g., Hernandez-Aguilar et al, 2007;Pruetz and Bertolani, 2007;Sanz and Morgan, 2009;Yamamoto et al, 2008). It is not surprising, given the extent of tool use by wild chimpanzees, that a wide array of tool-related tasks have been explored in captive apes, as well (e.g., Bania et al, 2009;Furlong et al, 2008;Limongelli et al, 1995;Mulcahy and Call, 2006;Povinelli, 2000;Tomasello et al, 1993;Tonooka et al, 1997;Visalberghi et al, 1995;Whiten et al, 1996).More recently, in contrast to reports of successful performance by chimpanzees on a range of tasks over the past several decades, Povinelli and his colleagues (2000) reported a series of some twenty-seven tool paradigms that resulted in poor performance by seven juvenile chimpanzees that had been laboratory-born and peer-reared as a separate social group. As a result, Povinelli (2000) reached a number of general conclusions about chimpanzees' abilities related to "folk physics".…”
mentioning
confidence: 99%
“…The inference that the differences are socially learned is based on (i) patterns of distribution that appear incompatible with genetic or simple environmental explanations; (ii) records of close observation of adults by infants as well as matching of mother-offspring foraging styles (4-7); and (iii) studies of both wild (8-10) and captive chimpanzees (11)(12)(13)(14)(15) showing that social learning from conspecifics can affect the acquisition of tool-use skills. Each wild chimpanzee community exhibits a distinct profile defined by several different kinds of putative traditions that have been described as cultures.…”
mentioning
confidence: 99%
“…However, what we really need to establish is whether chimpanzees learn from each other with sufficient fidelity for behavior to spread within a community. Thus far, only four experiments concern the spread of behavior at the group level (11,15,29,30). None of these investigations used a no-model control group, however, which might have demonstrated that the spread of behavior was not due to a gradual rise in individual learning.…”
mentioning
confidence: 99%